Evaluation of knowledge abort Act on the Professions of Nurse and Midwife by nursing and midwifery students, nurses and midwifes - Rozwadowska, Emilia; Krajewska-Kułak, Elżbieta; Kropiwnicka, Ewa; Lankau, Agnieszka; Lewko, Jolanta; Kowalczuk, Krystyna; Baranowska, Anna; Chilicka, Magdalena Anna; Damme-Ostapowicz, Katarzyna Van; Tołoczko, Helena; Wiśniewska, Anna; Trypuć, Marta; et al. (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Knowledge of valid regulations about nurse and midwife profession has fundamental meaning for nursing and midwifery faculty students as well as for practicing nurses and midwifes. Aim of study. Results analysis about knowledge of Act on the Professions of Nurse and Midwife (Journal of Laws of July 30, 1996) by bachelor nursery and midwifery students, master nursery students and working midwifes. Material and methods. Research was made on 129 bachelor nursery and midwifery students, master nursery students and working midwifes. For research was used original made questionnaire consisted of two parts: general and principal. Results. Obtained results enabled statement that most of the respondents recognised as false statement "nurse/midwife being European Union citizen cannot get profession licence in Polish territory", similarly as "nurse and midwifery professional secret duty ceased in the moment of patent’s death". According to problem "taking up nursery and midwife profession after 5 years break from diploma practise or after break in doing profession longer than five years is impossible" was shown considerable respondents ignorance. In issue that "nurse I obliged to give help in every case of risk of life, patent’s serious health injury according to own professional qualifications" almost all of the respondents answered correctly, just like in case that "nurse and midwifery are obliged to inform patient about his rights". Statement saying that "in extraordinary situations nurses and midwifes have a right refuse of doctor’s commend giving immediately reason of refusal on paper", correctly judged 100% midwifes and most of other researched groups. Conclusions. The greatest majority of responders pointed big knowledge of valid regulations for nurses and midwifes. The most of correct answers among of responders gave students from 2nd year of bachelor midwifery studies. Midwifery students gave more correct answers than nursery students. Question, in witch was given the least correct answers was connected with juridical restrains about legal form of health service. Conclusions. Predominant number of respondents proved broad knowledge of obligatory regulations about nursery and midwifery. Bachelor nursing students of the second year gave the most correct answers. The most intricate question turned out to be the inquiry about taking up nursig or midwifery profession after 5 years break. Nursing Topics 2010; 18 (4): 443-454